The role of Jovan Cvijić in a favourable outcome of the fight for the northern Slovenian boundaries and his influence on the Slovenian geogra - Josipovič, Damir (Anali PAZU HD, 2022)
The influence of Jovan Cvijić on the current image of the Slovenian nation, its geographical and spatial dimensions, including the boundary setting in space and time, as well as the significant impact of his scientific breadth on leading Slovenian geographers of 20th century, is almost unknown in Slovenia and therefore unrecognized. Hence, the article first presents the institutionalization of the Slovenian education system and the establishment of geography as an independent discipline in relation to the formation of today’s Slovenian national territory. In this context, it defines the circumstances of the linguistic integration of four varied and separate regional language standards into one that is going to become clearly separated from the other non-Slavic neighbours, but not from its Slavic hinterland. The paper analyses the historical role and importance of Jovan Cvijić in the process of building Slovenian national boundaries, especially the northern ones, as well as in relation to the ethno-psychological definitions of populations and their intrinsic demarcation. Finally, the paper assesses Cvijić’s influence on the disciplinary formation of Slovenian geographers.